Advances in Bio-Based and Biodegradable Polymeric Composites - Korzhikova-Vlakh, Evgenia G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint summarizes recent advances in the production and research of biobased and biodegradable polymeric composites for various applications. The development and characterization of environmentally friendly, conductive and biomedical materials as well as materials with barrier and antimicrobial properties have been considered and discussed.